Mix proportion for medium grade concrete with silica fume as cement replacement for general purpose construction - azida, Rashidi; Mohammad Ibrahim Safawi, M. Z.; Raudhah, Ahmadi (IOP Publishing, 2021)
There are many demands of concrete in construction leading to the use of industrial waste as mineral additive or supplementary filler to improve the concrete performance and lower production cost. Silica fume is a distinct industrial waste. The making of silica fume concrete is made by case basis based on specific needs especially for the production of prescribed High Performance Concretes. In this study, the use of silica fume for low/medium grade concrete for general production is investigated [1]. It is an attempt to find a mix proportion with recommended silica fume replacement to produce a medium grade concrete for general purpose construction. Silica fume as cement replacement greatly increase the mechanical and durability properties of concrete. The concrete mix with 10% silica fume replacement gives the most practical replacement percentage resulting to a 32% strength increase compared to concrete with no silica fume. It is also possible to produce a normal grade concrete using a standard M40 mix proportion. Concrete samples with less than 10% cement replacement did not show significant differences in mechanical and durability properties compared to the reference sample.